Synthesis and Anticonvulsant Evaluation of 3-(5-(4-substitutedphenyl)-4,5-dihydro-1H-pyrazol-3-ylamino)-2-(2-methylphenyl)quinazolin-4(3H)-one Derivatives - Kumar, Sachin; Jha, Keshari Kishore; Tripathi, Rati Kailash Prasad; Kumar, Nishant; Chaudhary, Anurag (Indian Journal of Pharmaceutical Education and Research, 2021)
ABSTRACT: Epilepsy arise due to discharge of electric current in CNS and it is Characterized by repeated seizure because of different factors like social, neurological and environmental or it may be due to genetic or non-genetic. A large number of AED’s used to treat epilepsy but all these shows drug resistance and side effects, so research interest continue to find out novel antiepileptic drugs with higher efficiency and less toxicity. A novel series of 3-(5-(4-substitutedphenyl)-4,5-dihydro-1H-pyrazole-3-ylamino)-2-(2-methylphenyl)quinazole4(3H)-one was developed, synthesized and evaluated for anticonvulsant activity using two pharmacological models, maximal electroshock seizure (MES) and subcutaneous pentylenetetrazole (scPTZ) models. Spectral data and elemental analysis were used to validate the structure of the synthetic compounds. Synthesized substances have also been tested for their neurotoxicity by rotary apparatus. Both compounds display strong anticonvulsant and neurotoxic activity. 3-(5-(4-fluorophenyl)-4,5-dihydro-1H-pyrazole-3-ylamino)-2-(2-methylphenyl)quinazole-4(3H)-one, 8(v) was found to be the most successful in maximal electroshock seizure (percentage protection = 73.63 at 150 mg/kg) and subcutaneous pentylenetetrazole induced convulsion model (percentage protection = 75.59 at 150 mg/kg) models and was found to be non-neurotoxic.
Keywords: AED’s; Qinazolin-4-(3H)-one; Anticonvulsant; MES; scPTZ; Neurotoxicity